Chemical quenching of singlet oxygen by plastoquinols and their oxidation products in Arabidopsis. (26th July 2018) - Ferretti, Ursula; Ciura, Joanna; Ksas, Brigitte; Rác, Marek; Sedlářová, Michaela; Kruk, Jerzy; Havaux, Michel; Pospíšil, Pavel
Summary: Prenylquinols (tocochromanols and plastoquinols) serve as efficient physical and chemical quenchers of singlet oxygen ( 1 O2 ) formed during high light stress in higher plants. Although quenching of 1 O2 by prenylquinols has been previously studied, direct evidence for chemical quenching of 1 O2 by plastoquinols and their oxidation products is limited in vivo . In the present study, the role of plastoquinol‐9 (PQH2 ‐9) in chemical quenching of 1 O2 was studied in Arabidopsis thaliana lines overexpressing the SOLANESYL DIPHOSPHATE SYNTHASE 1 gene (SPS1oex) involved in PQH2 ‐9 and plastochromanol‐8 biosynthesis. In this work, direct evidence for chemical quenching of 1 O2 by plastoquinols and their oxidation products is presented, which is obtained by microscopic techniques in vivo . Chemical quenching of 1 O2 was associated with consumption of PQH2 ‐9 and formation of its various oxidized forms. Oxidation of PQH2 ‐9 by 1 O2 leads to plastoquinone‐9 (PQ‐9), which is subsequently oxidized to hydroxyplastoquinone‐9 [PQ(OH)‐9]. We provide here evidence that oxidation of PQ(OH)‐9 by 1 O2 results in the formation of trihydroxyplastoquinone‐9 [PQ(OH)3 ‐9]. It is concluded here that PQH2 ‐9 serves as an efficient 1 O2 chemical quencher in Arabidopsis, and PQ(OH)3 ‐9 can be considered as a natural product of 1 O2 reaction with PQ(OH)‐9. The understanding of the mechanisms underlying 1 O2 chemical quenching provides information on the role of plastoquinols and their oxidation products in the response of plants to photooxidative stress. Significance Statement: In this study, direct evidence for chemical quenching of singlet oxygen by plastoquinols and their oxidized products and the formation of a natural product trihydroxyplastoquinone‐9 in vivo are reported. Comprehensive model for stepwise interaction of singlet oxygen with plastoquinols and their oxidized products during photooxidative stress in higher plants is discussed.